Does Nuclear Uncertainty Threaten Financial Markets? The Attention Paid to North Korean Nuclear Threats and Its Impact on South Korea's Financial Markets. Issue 1 (25th March 2018) - Huh, In; Pyun, Ju Hyun
Abstract : We explore how investor attention paid to dangerous nuclear tests influences financial market outcomes. To measure the attention paid to North Korean nuclear threats, we introduce a weekly Google search volume index for keywords on North Korean nuclear events. Using a time‐varying structural vector autoregression model with block exogeneity restrictions, we find that investor attention paid to nuclear threats has heterogeneous effects on South Korea's stock prices across industries and over time: attention on only the first nuclear test was negatively related to the stock price index, which vanished thereafter. Moreover, the investor attention paid to the nuclear risk reduced stock prices, especially in the banking industry, during the entire sample period.